SUSTAINABILITY ANALYSIS AT SIDOMULYO SMALLHOLDER COFFEE AGRO-INDUSTRY - Elida Novita; Rizal Syarief; Erliza Noor; Rubiyo Rubiyo (UPT Penerbitan Universitas Jember, 2012)
Sustainability of Sidomulyo smallholder coffee agro industry as a part of Jembercoffee agribusiness should be attempted by improving their high quality of coffee bean.Development of sustainability assessment indicators is needed to determine the factors thatare feasible to support coffee agro industry. Case studies conducted in smallholder coffeeplantation at Jember District, East Java. Through Rap-Coffee simulation, sustainabilitystatus is moderate (58.94%). Improving the status can be achieved based on the keyattributes of sustainability framework. Supports from stakeholders such as government,research institute and banking with incentives, credit, maintaining equipment and qualitystandards assistance would increase productivity and quality while improving smallholdercoffee prices.